Chinese-Speaking Learners' Cognitive Comprehension Problems with English Video-Based Materials. (July 2014) - Lin, Lu-Fang
This study surveyed the problems 213 university students confronted while viewing an online video-based English program. Data were collected through self-reports and one-to-one interviews. The content analysis approach was used. Totally, 18 problems were identified and categorized into three cognitive-processing stages: perception, parsing, and utilization. Percentages for each problem were calculated for the whole group and for the three English proficiency groups. The whole group results indicated that most comprehension problems occurred at the perception stage, and that the most common perception problem was that the speech rate was too fast. The most common parsing problem was that the participants failed to form a mental representation of what they had heard or read, while the most common utilization problem was that they could not assign the intended meanings to words. Each proficiency group's problems at the three cognitive stages were interpreted. Instructional recommendations to enhance learners' video comprehension are presented.